A protocol for a randomised, double-blind, placebo-controlled study of the effect of LIraglutide on left VEntricular function in chronic heart failure patients with and without type 2 diabetes (The LIVE Study). Issue 5 (20th May 2014) - Jorsal, Anders; Wiggers, Henrik; Holmager, Pernille; Nilsson, Brian; Nielsen, Roni; Boesgaard, Trine Welløv; Kumme, Anja; Møller, Jacob Eifer; Videbæk, Lars; Kistorp, Caroline; Gustafsson, Ida; Tarnow, Lise; et al.
Abstract : Introduction: Heart failure is one of the most common cardiovascular complications of diabetes and the most disabling and deadly complication too. Many antidiabetic agents have been associated with increased morbidity and mortality in a subset of patients with chronic heart failure (CHF); thus, new treatment modalities are warranted. Interestingly, a beneficial effect of the incretin hormone, GLP-1, on cardiac function has been suggested in patients with diabetes and patients without diabetes. Liraglutide (Victoza) is a GLP-1 analogue developed for the treatment of type 2 diabetes (T2D); however, its impact on cardiac function has not previously been investigated in patients with CHF. This prompted us to investigate whether liraglutide treatment for 24 weeks improves left ventricular ejection fraction (LVEF) in patients with CHF with and without T2D compared with placebo treatment. Methods and analysis: An investigator-initiated, multicentre, randomised, double-blind, parallel, placebo-controlled intervention trial. In total, 240 patients with CHF (with and without T2D) with LVEF≤45% will be randomised to either subcutaneous injection of liraglutide 1.8 mg or matching placebo once daily for 24 weeks. The effect of liraglutide on left ventricular function will be evaluated by advanced echocardiography, including three-dimensional contrast echocardiography. Ethics and dissemination: The study will be performed and monitored according to the Good Clinical Practice-International Conference on Harmonisation (GCP-ICH) regulations and conducted according to the principles of the Helsinki Declaration. The Danish Medicines Agency, the local Research Ethics Committee and the Danish Data Protection Agency have approved the study. Trial registration number: ClinicalTrials.gov Identifier: NCT01472640 .